Analysis of Sharia and Aqidah Values in the Ngejalang Tradition as a Source of Learning in Islamic Religious Education - Dwi Purwanto; Yuberti Yuberti; Devi Sela Eka Selvia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is driven by the urgent need to explore Islamic Religious Education (PAI) learning resources rooted in local wisdom, specifically focusing on the integrative acculturation within the Ngejalang tradition of the Lampung Saibatin community in Pekon Gunung Kemala Timur. Amidst modernization, this tradition persists as a vital cultural identity containing significant educational content, yet it faces the risk of shifting meanings if not formally reconstructed as scientific learning material. Consequently, this study aims to analyze the fundamental values of faith, sharia, and morals within the Ngejalang tradition to position it as a contextual PAI resource. Employing a descriptive qualitative method with an ethnopedagogical approach, primary data was gathered through participant observation and in-depth interviews, utilizing interactive analysis to examine Ngejalang as 'urf sahih’ (sound custom). The findings reveal that Ngejalang represents a unique manifestation of acculturation that transforms pilgrimage rituals into instruments for strengthening the pillars of Islam. Faith is internalized through the concept of tauhid via tadzkiratul maut (remembrance of death), while sharia values are implemented through the principle of al-'aadatu muhakkamah, where Islamic law serves as an active filter for ritual processes. Furthermore, moral values are reflected in a